Role of indole derivative SS-68 in increasing the frequency range of cardiac rhythm control (reflex stimulation of the sinoatrial node) - Pavel A. Galenko-Yaroshevsky; Anatoly A. Nechepurenko; Tatiana G. Pokrovskaya; Nikolai L. Shimonovsky; Alexander S. Dukhanin; Konstantin F. Suzdalev; Polina D. Maslova; Natalia M. Makhnova; Vadim V. Shneivais; Valery G. Abushkevich; Anait V. Zelenskaya; Valeria V. Seletskaya; et al. (Belgorod National Research University, 2021)
Introduction: Cardiac pacing is indicated for sick sinus syndrome. It is performed with a pacemaker via electrodes implanted in the heart. This technique has several disadvantages. The search for alternative methods of cardiac pacing is underway. One of them is control of heart rhythm through stimulation of the tragus. Objective: To perform the reflex stimulation of the sinoatrial node and to study the influence of the SS-68 substance on it. Materials and methods: Two electrodes were fixed in the reflexogenic zone of rabbits' auricles, volleys of electrical impulses from an electrical stimulator were applied to the electrodes, and the synchronization range of volley frequency and cardiac contractions was recorded. This range was re-recorded again after injecting the SS-68 substance (2-phenyl-1-(3-pyrrolidine-1-cyclopropyl)-1H-indole hydrochloride) intravenously at a dose of 50 µg/kg. In other experiments on frogs in a high-frequency electromagnetic field, the process of excitation of the area of the medulla oblongata associated with the heart rhythm was visualized. After the application of SS-68 (50 μM) to the surface of this zone, the process of its excitation was recorded. Results and discussion: Stimulation of the auricular reflexogenic zone of rabbits produced a synchronization of volley frequency and heart rate in the range from 173.5 ± 2.0 to 214.0 ± 1.8 per minute. SS-68 extended this range from 168.2 ± 1.9 to 219.4 ± 1.5 per minute. In the frog's medulla oblongata, an area synchronous to the heart rhythm glowed in the high-frequency electromagnetic field. SS-68 increased the area of glow by 131.0%. Conclusion: The substance SS-68 increases the frequency range of heart rhythm control by activating reflex stimulation of the sinoatrial node. The main point of application of SS-68 is the medulla oblongata. Glow in the high-frequency electromagnetic field reflects the process of neuron excitation. The increase in the glow zone under the influence of SS-68 indicates synchronously excited neurons, which leads to the assimilation of the central heart rhythm generation by the sinoatrial node.